Simultaneous Past and Present in The Sea - Li, Lianghui (ABEI Journal, 2021)
Time is complex in Banville’s novels in that they constantly feature tense switching, chronological confusion, and characters who are always casting a look back to the past for an escape from the present. In The Sea, Banville’s experimentation with tenses reflects his conception of time, particularly, the complex relationship between past and present. Part one of this article, focusing on Max’s childhood memory, examines how the blurring of the past and present selves, resulting from frequent tense switching and the notable use of the historical present, destabilizes the temporal gap between the narrator and the narrated within retrospective narration. Part two, concerning Max’s present, proposes to compare the portrayal of the present-day Cedars in the two parts of the novel, and proves the present to be elusive since Max’s experience is not contemporaneous with the time of narration. Drawing on Max’s various experiences of an alternative space, part three proceeds to argue that Max’s entire act of narration constructs a similar alternative space where past and present are engendered simultaneously. The dubious existence of the self in this alternative space suggests a defiance against the deictic center as I- herenow.